Transition and the Gifted - Between Identification and Non-Recognition - Minić, Jelena Lj. (Sociološki pregled, 2019)
The goal of this paper is to call the attention of the scientific and professional communities to the importance of support and help that gifted pupils need in the process of upbringing and education as well as to the importance of organizing a teaching process based on the principle of individuation. The paper points out the significance of the early identification of the gifted pupils and also the role of the society in encouraging the development of giftedness.The question that arises is whether the societies in transition recognize giftedness as personal, family and social potentials and whether they take appropriate measures for further development and optimal education and upbringing which will result in the actualization of giftedness and reduction of failure. In order to answer these questions, a systematic and continuous work of all responsible persons is needed, as well as a broad research which would reveal the current conditions in our school system.
Keywords: giftedness; identification; failure; transition